The Effectiveness of Benson Relaxation Therapy Through Family Empowerment on Reducing Blood Pressure in Hypertensive Elderly - Kasim, Febby Wahyunita; Nurhayati, Nurhayati; Muhaimin, Toha; Anwar, Syamsul; Basri, Achmad Ali (Universitas Pendidikan Indonesia, 2023)
Introduction. Hypertension is a degenerative disease affecting all ages, especially the elderly. This condition with poor management can cause fatal complications. One of the interventions to reduce blood pressure is the Benson relaxation technique which is very simple and can be practiced by patients themselves. This study aims to explore the effectiveness of Benson relaxation therapy through family empowerment on lowering blood pressure in the elderly with hypertension. Method. This research is quantitative with a pretest and post-test study design. A total of 44 respondents agreed to participate divided into intervention and control groups. This study was conducted in three three-month periods of data collection (July-September 2023) at one of the community health centers, in Indonesia. Instruments used in this study are measuring demographic characteristics and blood pressure observation. Result. The majority of respondents were aged 55-65 years old (54.5%) and female. There was a statistically significant effect of Benson Relaxation therapy through family empowerment on blood pressure in elderly hypertension with p-value 0.005. Discussion. It can be concluded that Benson Relaxation therapy through Family Empowerment is effective on the fourth day of measurement in reducing systolic blood pressure and effective on the third day of measurement in reducing diastolic blood pressure in the elderly with hypertension.